The context of disclosing suicidality: An exploration with attempt survivors. (19th November 2021) - Sheehan, Lindsay; Oexle, Nathalie; Armas, Silvia A.; Wan, Hoi Ting; Bushman, Michael; Glover, LaToya; Lewy, Stanley; Laique, Aamir
Abstract: Suicide attempt survivors selectively disclose suicidal ideation and suicide attempts. However, little is known about how suicide attempt survivors make these disclosure decisions. To address the dearth of research on the context of suicide disclosure, a community‐based participatory research team analyzed qualitative data from suicide attempt survivors ( n = 40) to examine when, how, and to whom they disclose suicidality. We describe findings on three main themes: (1) who to tell, (2) when to tell, and (3) how to tell. Within subthemes, we provide examples of diverse disclosure‐related strategies, including gradual disclosure, adapting disclosure to the audience, and determining the emotional readiness of both discloser and confidant. Counselors can use the study results to aid suicide attempt survivors in making disclosure decisions and crafting disclosure messages that maximize benefits for suicide attempt survivors and those to whom they disclose.